Precipitation sequence of an aged Al-Mg-Si alloy - Fang X.; Song M.; Li K.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Heat treatable Al-Mg-Si alloys can be strengthened via the precipitation of metastable phase particles. The precipitation sequence of an Al-0.89Mg-0.75Si alloy with trace Fe and Zn elements during aging at 180 °C has been investigated by transmission electron microscope (TEM), high resolution transmission electron microscope (HRTEM) and hardness measurements. It has been shown that the precipitation sequence of the alloy can be identified as follows: supersaturated solid solution → G.P. zones → metastable β″ precipitates → metastable β′ precipitates → stable β phase + Si particles. It is indicated that β″ phase remains stable up to 30 hours at 180°C. The hardness measurements during aging realize that the main strengthening phase for the investigated Al-Mg-Si alloy is β″ precipitates and the maximum hardness is obtained after aging at 180 °C for 4~6.5 hours.